Usage of Magnetorheological Damper in Active Front Bumper System for Frontal Impact Protection - Pokaad, Alif Zulfakar; Khisbullah , Hudha; Md Radzai , Said (2013)
In this paper, the effectiveness of the active bumper system to reduce the jerk of a vehicle during collision is discussed. The mathematical model is done by using MATLAB 7.0 to simulate a collision between a pendulum and a vehicle installed with the active bumper system. In the active bumper system, it consists of three parts which are magnetorheological(MR) model, inner controller and outer loop controller. The validated model is used to develop an inner loop controller by implementing a close-loop PI control to track the desired damping force through simulation. The governing equations of motions of vehicle collision and MR damper model are then integrated with the well known control strategy namely skyhook control. The performance of skyhook control is then compared with the vehicle with passive damper and common vehicle by using computer simulation in order to reduce the acceleration and the jerk of the vehicle during collision.